Reflective Practices in Learning Turkish Pronunciation as a Foreign Language - Duygu AK BAŞOĞUL; Cansu AKSU RAFFARD (Mehmet KURUDAYIOĞLU, 2018)
In this study, the aim is to raise the awareness of learners of Turkish as a foreign/second language by using reflective thinking stages (recalling experiences, researching causes, trying to change and improve experiences) and to improve their experiences by presenting solutions to the phonetic errors they frequently made in their pronunciation. The research is a qualitative study, and it is based on Bartlett's reflective teaching stages (mapping, informing, contesting, appraising and acting). The implementation stage lasted 8 class hours (400 minutes), consisting of two hours per week, at A2 level at the TÖMER İzmir branch of Ankara University. Following each implementation, reflections on the teaching process were obtained thanks to the diaries kept by both the learners and the researcher who carried out the implementation and created course reports, course records were formed and peer evaluations were obtained and, when needed, rearrangements were made. At the end of the implementation phase, the data obtained through the interviews with teachers and learners about the process, the findings of the new teaching process on the usefulness of work and the level of awareness for pronunciation were shared with the instructors and learners. It was concluded that the implementation led to a positive development in learners and that they acquired communicative skills by finding the opportunity to do speaking practice, through the reflective practices performed.